Marital Satisfaction amongst Nigerian Immigrants in North America (NINA): Pilot Study (Asian Journal of Social Science Studies, 2019)
Background: It has been observed that some Nigerian Families that immigrated to North America (NINA) seem to have very stressful marital relationships that lead to separation or divorce. The goal of this study was to determine the level of marital satisfaction among NINA Method: A simple, standardized survey tool was utilized to measure the index of marital satisfaction (IMS). The score varied from 0-100 with a lower score (